Effects of strength training on postpubertal adolescent distance runners - Blagrove, R. C.; Howe, L. P.; Cushion, E. J.; Spence, A.; Howatson, G.; Pedlar, C. R.; Hayes, P. R. (Medicine & Science in Sports & Exercise, 2018)
PURPOSE: Strength training activities have consistently been shown to improve running economy (RE) and neuromuscular characteristics, such as force-producing ability and maximal speed, in adult distance runners. However, the effects on adolescent (<18 yr) runners remains elusive. This randomized control trial aimed to examine the effect of strength training on several important physiological and neuromuscular qualities associated with distance running performance.